Liquid Encapsulation in Parylene Microstructures Using Integrated Annular-Plate Stiction Valves - Christian A. Gutierrez; Ellis Meng (Micromachines, 2011)
We report the design, fabrication and characterization of micromachined Parylene structures for self-sealing liquid encapsulation applications. Automatic sealing is enabled through the use of an integrated annular-plate stiction valve which greatly reduces device footprint over in-plane configurations. We achieve automatic wafer-level liquid entrapment without using adhesives or processing at elevated pressures or temperatures. The ability to track changes to the internal liquid volume through the use of electrochemical impedance measurements is also presented.